TREM-1 promotes intestinal tumorigenesis. Issue 1 (December 2017) - Saurer, Leslie; Zysset, Daniel; Rihs, Silvia; Mager, Lukas; Gusberti, Matteo; Simillion, Cedric; Lugli, Alessandro; Zlobec, Inti; Krebs, Philippe; Mueller, Christoph
Abstract Triggering receptor expressed on myeloid cells-1 (TREM-1) is a potent amplifier of pro-inflammatory innate immune responses. Increasing evidence suggests a role for TREM-1 not only in acute pathogen-induced reactions but also in chronic and non-infectious inflammatory disorders, including various types of cancer. Here, we demonstrate that genetic deficiency inTrem1 protects from colorectal cancer. In particular, Trem1 −/− mice exhibited reduced tumor numbers and load in an experimental model of inflammation-driven tumorigenesis. Gene expression analysis ofTrem1 −/− versusTrem1 +/+ tumor tissue demonstrated distinct immune signatures. WhereasTrem1 −/− tumors showed an increased abundance of transcripts linked to adaptive immunity, Trem1 +/+ tumors were characterized by overexpression of innate pro-inflammatory genes associated with tumorigenesis. Compared to adjacent tumor-free colonic mucosa, expression ofTrem1 was increased in murine and human colorectal tumors. Unexpectedly, TREM-1 was not detected on tumor-associated Ly6C− MHC class II+ macrophages. In contrast, TREM-1 was highly expressed by tumor-infiltrating neutrophils which represented the predominant myeloid population inTrem1 +/+ but not inTrem1 −/− tumors. Collectively, our findings demonstrate a clear role of TREM-1 for intestinal tumorigenesis and indicate TREM-1-expressing neutrophils as critical players in colorectal tumor development.